2023
DOI: 10.1073/pnas.2301301120
|View full text |Cite
|
Sign up to set email alerts
|

SoxC transcription factors shape the epigenetic landscape to establish competence for sensory differentiation in the mammalian organ of Corti

Abstract: The auditory organ of Corti is comprised of only two major cell types—the mechanosensory hair cells and their associated supporting cells—both specified from a single pool of prosensory progenitors in the cochlear duct. Here, we show that competence to respond to Atoh1, a transcriptional master regulator necessary and sufficient for induction of mechanosensory hair cells, is established in the prosensory progenitors between E12.0 and 13.5. The transition to the competent state is rapid and is associated with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…In the mouse inner ear, the SoxC subfamily members Sox4 and Sox11 are co-expressed in proliferating hair cell progenitor cells and newly born hair cells, and in combination are essential for hair cell formation ( Gnedeva and Hudspeth, 2015 ; Wang et al, 2023 ). Ectopic expression of either gene converts supporting cells to hair cells ( Gnedeva and Hudspeth, 2015 ; Wang et al, 2023 ). A recent study showed that Sox4 confers hair-cell competence by binding lineage-specific regulatory elements and making these accessible ( Wang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mouse inner ear, the SoxC subfamily members Sox4 and Sox11 are co-expressed in proliferating hair cell progenitor cells and newly born hair cells, and in combination are essential for hair cell formation ( Gnedeva and Hudspeth, 2015 ; Wang et al, 2023 ). Ectopic expression of either gene converts supporting cells to hair cells ( Gnedeva and Hudspeth, 2015 ; Wang et al, 2023 ). A recent study showed that Sox4 confers hair-cell competence by binding lineage-specific regulatory elements and making these accessible ( Wang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic expression of either gene converts supporting cells to hair cells ( Gnedeva and Hudspeth, 2015 ; Wang et al, 2023 ). A recent study showed that Sox4 confers hair-cell competence by binding lineage-specific regulatory elements and making these accessible ( Wang et al, 2023 ). Although neither Sox4 nor Sox11 was present in the paddlefish lateral line-enriched gene-set ( Modrell et al, 2017a ), we cloned sterlet Sox4 , which proved to be expressed in both ampullary organs and neuromasts, though more strongly in ampullary organs ( Figures 2I, J ).…”
Section: Resultsmentioning
confidence: 99%
“…As described above, vertebrate inner ear and lateral line hair cells develop from patches of prosensory tissue marked by Sox2 , a member of the SoxB transcription family ( Neves et al, 2013 ). SoxC family members, such as Sox4 and Sox11 then act within these patches to provide competence for differentiation of hair cells and supporting cells ( Gnedeva and Hudspeth, 2015 ; Wang et al, 2023 ). Cells within this expression domain upregulate the proneural transcription factor Atoh1 , which initially marks the progenitors of both hair cells and supporting cells ( Yang et al, 2010 ; Li et al, 2022 ).…”
Section: Evolutionary Relationships Between Vertebrate and Invertebra...mentioning
confidence: 99%
“…By binding to the minor groove of DNA, SOX4 alters chromatin architecture, leading to changes in transcriptional activities of downstream genes. SOX4 (and SOX11) has pleiotropic functions, which are likely to be mediated by distinct regulatory elements and downstream target genes involved in multiple developmental processes, including neurogenesis [18,19], heart development [10] and skeletal patterning [20], but also lymphocyte maturation [21] and more recently development of the inner ear [22]. The specific target genes of SOX4 have not yet been fully defined, but, among the genes that have been shown to be regulated by SOX4, some are important for neurodevelopment and disease (e.g., RELN, DCX, and WDR45) [19,23].…”
Section: Sox4 Structure and Functionmentioning
confidence: 99%